Company Profile Design Based Interactive Multimedia as Information Media: Case study: CV. Rizka Multti Dimensi Semarang Regency - Ahmad Wahyudin; Fitro Nur Hakim (International Journal of Graphic Design, 2024)
Competition in information technology is currently growing rapidly, the printing business in Indonesia that uses digital machines or offset machines is increasing. One of them is CV. Rizka Multi Dimensi, as a printing company in the Semarang Regency area which has been established for more than 10 years requires the right marketing strategy and information. Not only to face competition but also to maintain long-term existence. CV. Riska Multi Dimensi still uses printed company profiles , such as brochures, business cards and banners, so it is very difficult to compete with other companies, especially in the information sector. The company profile type of printed media is only in the form of writing and can only provide visuals in the form of images to represent all the information, the production costs are expensive plus the materials used are usually easy to tear, meaning that mechanical interference is high so that the information received is incomplete.Designing an interactive multimedia company profile is a medium for conveying information that can be a solution for introducing the outside world about a company profile, about services that have been provided, as well as products that have been made by the company in an interactive way that is easy to remember, so that it can achieve its goals. a big role in building a company's identity.By creating an interactive company profile that visualizes an Adobe Flash program in a combination of media such as text, images (JPG/PNG/TIF) , video (FLV/AVI/MP4), animation ( SWF) , and sound, it will make the application more attractive, so buyers more interested in understanding the company's identity through the company profile. The media expert's validation score is 32 and the material expert's score is 38, so the product is categorized as very valid for use as an interactive e- company profile , and the user's score regarding the product is 36.75, which means it is valid for use.